T(n)=n+T(2n-1)

Simple and best practice solution for T(n)=n+T(2n-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for T(n)=n+T(2n-1) equation:



(T)=T+(2T-1)
We move all terms to the left:
(T)-(T+(2T-1))=0
We calculate terms in parentheses: -(T+(2T-1)), so:
T+(2T-1)
We get rid of parentheses
T+2T-1
We add all the numbers together, and all the variables
3T-1
Back to the equation:
-(3T-1)
We get rid of parentheses
T-3T+1=0
We add all the numbers together, and all the variables
-2T+1=0
We move all terms containing T to the left, all other terms to the right
-2T=-1
T=-1/-2
T=1/2

See similar equations:

| 4=q+1 | | 7x-3(x-1)=15 | | 2(x-1)+3(x-2)=4x-3 | | 2(6x-5)-8x=14 | | 3x+4∘+8x−28∘=108∘ | | 7x+54=-2 | | 4(3x-1)-9=11 | | 4x-12=31 | | 3x-7=-3x | | x+1/6=-3/5 | | 12a(24)=4 | | 35x+3=45+2x | | x/3+15=40 | | 4(3x-1)9x=11 | | 4x+2=1x+3 | | x+46=3x-1 | | 6(x-3)+5=-7 | | x/5-13=34 | | 7+p+9=`17 | | -2(w-4)=-8w-46 | | 14p-(3p-2)-12-(5p+2-(p-1)=|-34 | | x+2(3x-2)=17 | | 7y-42=5(y-8) | | 8q-12=8q-12 | | Y+7x=33 | | 2(v-5)=-9v+45 | | -6+z=22 | | -10=r-4+ -6 | | 4w-15w=-44 | | -2x-3=-2x+8 | | 5x+2=1x+0 | | 5(u+6)=-2u-5 |

Equations solver categories